LOCAL WISDOM-BASED CROSS CULTURAL MANAGEMENT - Andi Yusniar Mendo (Journal of International Conference Proceedings (JICP), 2019)
The culture of local wisdom which constructive with the community living dynamic such as the honesty, firmness, toghetherness, trust and pride as the value in social interaction in a system. The cross-cultural management born from the local wisdom as the community living system. The system of culture management in community include the religion, language, economy, technology, education, social organization, politic and art systems. The cross-cultural management as the main asset by state to progress with identity which own. Include Indonesia today to know the important of local wisdom which always to be grow suitable with the community culture. These study used of public option survey based on the opinion of community which actualization in qualitative research which used of descriptive. The result of research to found that the cross-cultural management which important to develop suitable with the existence in now and in the future. The fundament of culture management to see from the value, norm, clausal, philosophy and principle have actualization in spesific the cross-culture in Indonesia. The cross-cultural management based on local wisdom represent the united progress century. That mean the community which varians of local wisdom from the cross-culture to progress of united century. The cross-culture management represent the important instrument to direction of community have the local wisdom as an adhesive for the progress of the nation.